Factors affecting addiction severity index (ASI) among clients enrolled in methadone maintenance treatment (MMT) program in Myanmar - Sun Tun; B. Vicknasingam; Darshan Singh (BMC, 2021)
Abstract Background Opioid substitution with methadone maintenance treatment (MMT) is shown to reduce illicit opioid use and renew social functioning. Understanding factors that undermine clients' social functioning during MMT treatment is vital for improving treatment compliance and quality of life. Method A total of 210 respondents who were already enrolled in a formal MMT program in Myanmar were recruited from five cities through stratified random sampling for this cross-sectional study. The addiction severity index (ASI) was used to objectively assess respondents social functioning in the last 30 days. Higher ASI scores denote poorer social functioning. Result Respondents total ASI scores in the respective domains were: employment (47.4%), alcohol (44.4%), drug use (7.2%), legal (49.2%) and social-family relationship (10.7%). Those reported to have never injected drugs in the last 30 days had lower ASI total scores than those who reported injection drug use (p = 0.01). After identifying the differences in ASI total scores, we found there were significant associations in the clients' hepatitis C status, age category, frequency of heroin injection, quality of life score, marital status, current leisure status with family/friend, current history of injection in the last 30 days, income status, satisfaction with current marital status, as well as reported drug and alcohol use (p < 0.05). Stepwise binary logistic regression showed that alcohol and higher frequency of heroin injection were associated with higher ASI scores. Meanwhile, older age, respondents those who had leisure time with family, and satisfied with current marital status had lower ASI scores (p < 0.05). Conclusion Our results indicate that those enrolled in the MMT program in Myanmar faced many challenges in their daily social functioning. Treatment providers must take heed of these apparent impediment to ensure clients chequered social functioning does not undermine their treatment compliance. Trial registration: NA